SISTEM PENGAKUTAN SAMPAH DI KOTA MEULABOH - Meidia Refiyanni (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
Sabang city is one of the major tourist destinations in Aceh province and needs to ensure its area is in a low-risk flood inundation zone. However Sabang city has not had a good and comprehensive drainage system yet and often experienced flood. Its Sabang's topographical feature which consists of mountains, hills, and plains, has caused the drainage system of Sabang to be unique and special. According to Sabang Spatial Plan Year 2012 to 2017, Sabang should improve the function of its drainage infrastructures immediately. Nonetheless, due to budget constraints it is necessary to determine the handling priority of drainage system of Sabang city during the next 20 years. Determination of handling priority of Sabang’s drainage system is based on the physical, demographic, and environmental aspect and is in accordance with survey results and analysis of secondary data. The selection of priority of service areas is performed by weighted average method. Based on the analysis of the three factors described above, it can be seen that the handling priority of subwatershed for short-term is in subwatershed Anoi Itam, subwatershed Krueng Balohan and sub- watershed Pria Laot; medium-term is in subwatershed Keunekai, subwatershed Ceunohot, subwatershed Aneuk laot, subwatershed Paya Seunara; and long-term is in subwatershed Ceuhum, subwatershed Ujung Bau, subwatershed Gua Sarang, subwatershed Teupin Kareung and subwatershed Iboih. Keywords : Priority, drainage system, weighting average, Sabang city